2016
DOI: 10.1111/1365-2664.12582
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous declines in summer survival of three shorebird species signals a flyway at risk

Abstract: Summary1. There is increasing concern about the world's animal migrations. With many land-use and climatological changes occurring simultaneously, pinning down the causes of large-scale conservation problems requires sophisticated and data-intensive approaches. 2. Declining shorebird numbers along the East Asian-Australasian Flyway, in combination with data on habitat loss along the Yellow Sea (where these birds refuel during long-distance migrations), indicate a flyway under threat. 3. If habitat loss at stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
219
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(234 citation statements)
references
References 41 publications
(99 reference statements)
8
219
0
Order By: Relevance
“…The current loss of intertidal habitats has resulted in increasing concentrations of birds at the remaining sites (Yang et al 2011) and is thought to be already adversely affecting shorebird populations (Conklin et al 2016;Piersma et al 2016). Significant further loss of habitat are already included in provincial development plans, but not all have yet been approved by the State Council (see above).…”
Section: A Future For Shorebirds On China's Yellow Sea Coast?mentioning
confidence: 99%
See 1 more Smart Citation
“…The current loss of intertidal habitats has resulted in increasing concentrations of birds at the remaining sites (Yang et al 2011) and is thought to be already adversely affecting shorebird populations (Conklin et al 2016;Piersma et al 2016). Significant further loss of habitat are already included in provincial development plans, but not all have yet been approved by the State Council (see above).…”
Section: A Future For Shorebirds On China's Yellow Sea Coast?mentioning
confidence: 99%
“…Murray et al (2014) estimate the area of China's tidal flats were~5398 km 2 in the 1950s,~2677 km 2 in the 1980s and, by the 2000s, had decreased to 1611 km 2 , with the average annual rate of loss since the 1980s being 1.8% per annum (p.a.) Piersma et al (2016), however, report an annual loss of 4% between 1990 and 2013. Nevertheless, the rate of loss is increasing; rates of land claim, which were~400 km 2 p.a.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a specific human-induced mortality, such as the effects of an oil spill (Votier et al (2005), or of habitat degradation in a specific part of their range Piersma et al (2015) can be modelled if sufficient data are available for the impacted population. Ideally, large numbers of individually marked birds are followed over their entire life, either through electronic tagging or by applying permanent marks that can be read from a distance, such as colour rings, or by standard, steel rings.…”
Section: Not All Seabirds Are Equalmentioning
confidence: 99%
“…Iwamura et al (2013) showed how a 30% loss of habitat in coastal areas such as East Asia's Yellow Sea might result in as much as a 70% decline in some shorebird populations due to the large percentage of some populations reliant on those habitats during migration. There is little doubt that the most pressing conservation need for migratory shorebirds reliant on coastal staging habitats in the EAAF is to ensure adequate protections for the remaining important coastal staging habitats in east Asia which are being lost at alarming rates (MacKinnon et al, 2012;Murray et al, 2014;Piersma et al, 2015). However, several shorebird species migrate across a broad front and use a wide variety of wetland habitats (Boere & Stroud, 2006;Hagemeijer, 2006), and conserving them requires broader strategies that account for the irregularity in suitability of many inland wetlands (Skagen & Knopf, 1993;Haig et al, 1998).…”
Section: The Importance Of Conserving Migratory and Highly Mobile Spementioning
confidence: 99%